Umrah Law Implementation: Performance Analysis of Al-Fazza Tour & Travel Agency Semarang - Naufal, Jiyadu; Rozaq, Abdul (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study analyzes the implementation dynamics of Law No. 14 of 2025 on Umrah Pilgrimage, specifically focusing on independent Umrah provisions within the operational context of Al-Fazza Tour & Travel Agency in Semarang. This phenomenon is examined to understand how organizations respond to regulations that may disrupt travel agencies' traditional roles. Utilizing a qualitative case study design, data were gathered through in-depth interviews with key management (the Director and Operations Manager) and participant observation. Results indicate that regulatory implementation is interpretative and adaptive, avoiding radical structural shifts. Management perceives the regulation through three primary lenses: legal legitimacy, new competitive challenges, and catalysts for strategic adaptation. Empirically, the legalization of independent Umrah has not significantly decreased pilgrim interest, as trust, service comfort, and the need for religious guidance remain dominant preferences. The agency’s adaptive response prioritizes educational functions through community outreach regarding the technical complexities and risks of independent Umrah. Theoretically, this research enriches bottom-up policy implementation studies in the religious service sector and recommends optimizing spiritual guidance as a core strategy for organizational sustainability amidst regulatory changes.